The limits of the legal complex : Nordic lawyers and political liberalism - Feeley, Malcolm M.; Langford, Malcolm (Oxford : Oxford University Press, 2021)
Spanning two centuries and five Nordic countries, this book questions the view that political lawyers are required for the development of a liberal political regime. It combines cross-disciplinary theory and careful empirical case studies by country experts whose regional insights are brought to bear on wider global contexts.
This edition also issued in print: 2021.
"This is an open access publication, available online and distributed under the terms of a Creative Commons Attribution - Non Commercial - No Derivatives 4.0 International licence (CC BY-NC-ND 4.0)"--Title page verso.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from PDF title page (viewed on February 9, 2022).
Keywords: Law -- Scandinavia -- History; Lawyers -- Scandinavia -- History; Lawyers -- Political activity -- Scandinavia -- History; Law -- Political aspects -- Scandinavia -- History; Liberalism -- Scandinavia -- History; Law; Laws of specific jurisdictions & specific areas of law